Intraoperative frozen section analysis of margin status as a quality indicator in gastric cancer surgery. Issue 1 (30th September 2022) - Watanabe, Akie; Adamson, Hannah; Lim, Howard; McFadden, Andrew F.; McConnell, Yarrow J.; Hamilton, Trevor D.
Abstract: Introduction: Positive pathologic margins following gastric cancer (GC) resection carries a poor prognosis. We evaluated intraoperative frozen section (IFS) analysis of resection margins (RMs) as a quality indicator in GC surgery. Methods: Patients referred to a provincial cancer agency with surgically resected non‐metastatic GC between 2004 and 2012 were included. Associations between IFS analysis, other baseline characteristics, RMs, and overall survival (OS) were assessed using logistic regression, Kaplan−Meier analyses, and Cox proportional hazards modeling. Results: Among 377 patients, median age was 67 years, 68% were male, and 16% had +RMs. Thirty‐four percent of patients underwent IFS analysis, which protected against +RMs (odds ratio [OR]: 0.34, 95% confidence interval [CI]: 0.16−0.73, p  = 0.006) and improved OS (hazards ratio [HR]: 0.72, 95% CI: 0.54−0.98, p  = 0.037). OS following re‐resection of IFS positive patients was similar to IFS negative patients (69 vs. 54 months, p  = 0.317). Stage III disease (OR: 12.8, 95% CI: 3.00−55.0, p  = 0.001) and gastroesophageal junction tumors (OR: 2.25, 95% CI: 1.05−4.78, p  = 0.036) predicted +RMs. Stage III disease led to worse OS (HR: 2.89, 95% CI: 1.92−4.34, p  < 0.001) while intestinal histology improved OS (HR: 0.67, 95% CI: 0.50−0.90, p  = 0.007). Conclusions: IFS analysis reduce +RMs and improve OS and should be incorporated in curative intent GC surgery for patients with locally advanced GC.